Method of repairing of laptop batteries under constraints of limited resources - Artem Tetskyi; Artem Perepelitsyn; Olexander Zheltukhin (Авіаційно-космічна техніка та технологія, 2023)
The subject of study in this article and research is the process of reuse and recovery of power elements and batteries of modern digital electronics and laptop batteries, as well as controller diagnostic and repairing processes. The goal is to increase the duration of the lifetime and improve the maintainability and efficiency of reusing batteries of laptops and portable electronic devices. The task is to analyze existing types of laptop batteries; analyze different models of battery controllers; analyze options for repairing Li-ion batteries from secondary good market; propose a sequence of repairing of laptop batteries and portable electronics with use of Li-ion cells; and perform practical application of the research results. According to the tasks, the following results were obtained. The possibilities and existing options for repairing laptop batteries are analyzed. The possible mechanisms of protection of Li-ion batteries with different principles of action are analyzed. An analysis of the possibility of repairing of batteries with diagnostics of the elements in the laptop accumulator is performed. The process of repairing of the operation of laptop Li-ion batteries is proposed. A sequence for resetting error flags using additional equipment is proposed. The process of mechanical disassembling of the plastic housing of the laptop battery for the replacement of elements is described. The necessary equipment and tools for performing advanced diagnostics of laptop batteries are provided. A comparison of the results of the analysis of battery controllers and the practical experience of their recovery is performed. The description of the utility package for working with battery controllers is provided. Conclusions. The scientific novelty of the obtained results is in the fact that the comparative analysis of recovery methods of different models of batteries from different manufacturers allows to assess in advance the possibility of successful repairing of a laptop battery with a given controller. The proposed method of repairing of laptop batteries makes the recovery process predictable and reproducible for a wide range of battery models. The provided practical example of using the method demonstrates the possibility of obtaining additional information about batteries, even if the manufacturer does not provide documentation. The practical use of the research results allows to perform the process of repairing of a part of laptop battery models without additional knowledge and tools. It allows to reduce costs for the processes of maintaining the workability of electronics with extending of efficient device lifitime.